Análise de patentes por mapas mentais automatizados no desenvolvimento do conhecimento organizacional - Vanderlei, Celso Arruda (2018)
The development of organisational knowledge is one of the fundamental aspects of the innovation capacity of the organisations and consequently for the increase of the competitiveness in the local market and mainly in global contexts. Patent databases represent an essential source of information and technological know-how that are easily accessible to any organisation, but they are still little explored in this sense, due, among other factors, to the difficulties inherent in finding useful knowledge in particular situations from large volumes of data. The mind mapping technique as a facilitator of learning has been applied successfully in teaching and professional settings. In this sense, the objective of the research presented is to investigate how the mind map technique can be used in the discovery of organisational knowledge in patent bases. Adopting a phenomenological approach, the research strategy chosen is based on the concept of action research applied in two studies, the first in a small commercial enterprise, and the second in a large service company. Patents were analysed by mental maps on strategic themes for each organisation, with detailed monitoring and step-by-step registration of the participants in the discovery of patent knowledge by this method. The first study resulted in the development of new potential suppliers, led to the discussion about new possible markets for the organisation and identification of technological trends for the product lines in force in the period of the research. In the second study, the participating organisation identified more efficient technological alternatives for a major project in progress, opportunities for improvement of critical processes and possibilities of new business in waste recycling. The main contributions of this work are the development and public availability of the automated mechanism of patents mind map generation; in demonstrating the use of this mechanism in corporate environments; in the proposal of the use of mental maps as a complementary technique in the discovery of patent knowledge; and the broadening of the discussion on the possibilities of learning and developing innovations from patent databases using automated mind maps.